Study on Gravity Technique Measurements Associated with Different Lithologies in Turkana South Subcounty - Nyaberi, Daniel Mogaka (Research Advances in Environment, Geography and Earth Science Vol. 5, 2024)
The geology of Turkana South Subcounty encompasses the basement (The Neoproterozoic belt), the tertiary volcanics and the quaternary sediments with similarities across the border in eastern Uganda, and counties of West Pokot, Baringo, Samburu and area and Marsabit. The use of gravity data has demonstrated the capability for monitoring lithological changes in large-scale in as a consequence differentiating basement and sedimentary of buried valleys. Gravity anomalies are associated with lateral contrasts in density and therefore deformation by faulting or folding will be manifested if accompanied by lateral density changes, otherwise the vice versa is true. The objective of the study is to use the gravity data to advance geological interpretation in the region, especially looking at the subsurface structure of the basement and the relation of gravity in relation to the known geology of the area. The study has revealed that the regional anomaly gravity map presents high anomalies in the Northern region in the NW-SE trend and low anomalies in the southern trending in NW-SE, while the residual anomaly gravity map shows different trends for the low and high gravity anomalies. The gravity anomalies are well interpreted in line with the lithologies of the study area rather than the deformation of the same lithologies. There is observed high values of gravity anomaly values (ranging -880.2 to -501.2 g.u.) where there is eolian unconsolidated rocks overlying the basement as compared to low gravity anomaly values (ranging -1338.9 to -1088.7 g.u.) where the andesites, trachytes and phonolites overly the basement. The different regional gravity anomalies relate well with different rock densities in the study area along the line profile for the radially averaged power spectrum. The gravity highs are noted in the eastern point and are associated with andesites, trachytes, basalts and igneous rocks, while the gravity lows are associated with sandstone, greywacke, arkose, and eolian unconsolidated rock. The utilization of the information from the Power spectrum analysis demonstrates that the depth to the deepest basement rock is 12.8 km which is in the eastern flank, while the shallowest to the basement of 1.1 km to the western flank.